Hybridized Zoonotic Schistosoma Infections Result in Hybridized Morbidity Profiles: A Clinical Morbidity Study amongst Co-Infected Human Populations of Senegal - Fall, Cheikh B.; Lambert, Sébastien; Léger, Elsa (MDPI (Multidisciplinary Digital Publishing Institute), 2021)
Hybridization of infectious agents is a major emerging public and veterinary health concern at the interface of evolution, epidemiology, and control. Whilst evidence of the extent of hybridization amongst parasites is increasing, their impact on morbidity remains largely unknown. This may be predicted to be particularly pertinent where parasites of animals with contrasting pathogenicity viably hybridize with human parasites. Recent research has revealed that viable zoonotic hybrids between human urogenital Schistosoma haematobium with intestinal Schistosoma species of livestock, notably Schistosoma bovis, can be highly prevalent across Africa and beyond. Examining human populations in Senegal, we found increased hepatic but decreased urogenital morbidity, and reduced improvement following treatment with praziquantel, in those infected with zoonotic hybrids compared to non-hybrids. Our results have implications for effective monitoring and evaluation of control programmes, and demonstrate for the first time the potential impact of parasite hybridizations on host morbidity.
Microorganisms 2021, 9, 1776
Keywords: hybridization; schistosomiasis; morbidity; ultrasonography; disease control; one health; CEA-AGIR; Université Cheikh Anta Diop; Sénégal; Lucy Yasenev; Amadou Djirmay Garba; Samba D. Diop; Anna Borlase; Stefano Catalano; Babacar Faye; Martin Walker; Mariama Sene; Joanne P. Webster